The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s1413-41522015020040075357
|View full text |Cite
|
Sign up to set email alerts
|

Remoção de matéria orgânica do esgoto em solo de wetland construído

Abstract: RESUMO Nos sistemas wetlands construídos os meios suportes tradicionalmente utilizados são areia grossa, cascalho, pedregulho e brita. Nesta pesquisa, foi utilizado o solo natural (Latossolo Vermelho-Amarelo) misturado com areia média, plantado (wetlands construídos) com arroz irrigado (Oryza sativa L.) ou não (controles). O objetivo foi avaliar a remoção de DBO dos esgotos domésticos pelos processos de imobilização do carbono da biomassa microbiana e da respiração basal (atividade microbiana). Foram utilizado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
2
1
2
Order By: Relevance
“…It was however lower than that Silva et al (2015) obtained (97 to 99%) especially because of the association of the use of coarse sand, gravel, and crushed gravel in a same CW. In this study, only gravel #2 was used as a support medium, which resulted in high efficiency in the removal of suspended and sedimentable solids, although allowing the passage of particulate organic matter, which could be greatly increased by using a support medium consisting of sand, as stated by Silva et al (2015), and consequently, of particulate BOD. Ali et al (2018) had already observed an overall maximum decrease of 82% in BOD 5,20 .…”
Section: Physical and Chemical Attributes Of Raw Sewage (Rs) Influent And Effluent Of Cultivated Beds (Cw)contrasting
confidence: 70%
“…It was however lower than that Silva et al (2015) obtained (97 to 99%) especially because of the association of the use of coarse sand, gravel, and crushed gravel in a same CW. In this study, only gravel #2 was used as a support medium, which resulted in high efficiency in the removal of suspended and sedimentable solids, although allowing the passage of particulate organic matter, which could be greatly increased by using a support medium consisting of sand, as stated by Silva et al (2015), and consequently, of particulate BOD. Ali et al (2018) had already observed an overall maximum decrease of 82% in BOD 5,20 .…”
Section: Physical and Chemical Attributes Of Raw Sewage (Rs) Influent And Effluent Of Cultivated Beds (Cw)contrasting
confidence: 70%
“…High values of COD reduction in phytotreatment systems are quite common and are associated with the increase of oxygenation that the plants promote in the environment and allow greater assimilation of C by microorganisms (Caselles-Osorio & Garcia, 2007). Silva, Bernardes, and Ramos (2015) verified the influence of the root system on stimulating the decomposition of organic matter and assimilation of carbon for microorganisms. Efficient removals were observed in Typha latifolia, 78 and 92% in municipal sewage, Typha angustifolia, 68% in anaerobic effluents from pig farming (Chung, Wu, Tam, & Wong, 2008) and in systems with Pontederia sagittata, 80% in the treatment of sugarcane residue (Ólguin, Sánchez-Galván, González-Portela, & López-Vela, 2008).…”
Section: Cod Total Alkalinity Sst and Ssvmentioning
confidence: 86%
“…In wetland soils constructed to treat domestic sewage, the greater the microbial activity, the better, as this will ensure the greatest possible removal of MO present in the sewage, mineralized and removed from the sewage (Silva et al, 2015).…”
Section: Cod Total Alkalinity Sst and Ssvmentioning
confidence: 99%
“…As Wetlands construídas (WC) apresentam condições para formar um sistema de pós-tratamento bastante completo e eficiente, sobretudo para efluentes anaeróbios, uma vez que, apresentam elevada capacidade de remoção de Demanda Bioquímica de Oxigênio (DBO5) (SILVA;BERNARDES;RAMOS, 2015;CALIJURI et al, 2009). Alguns estudos demonstraram que esta tecnologia chega a apresentar eficiência na remoção de DBO de 80% (CALIJURI et al, 2009), 81-89% (RAMOS et al, 2017 e 97-99% (SILVA; BERNARDES; RAMOS, 2015).…”
Section: Introductionunclassified